Agritourism as a catalyst for sustainable rural development: Exploring its multifunctional prospects - Sharma, Saurabh; Maisnam, Guneshori; Thangjam, Deepa; Choudhary, Ravish; Kirbag, Sevda; Sushkova, Svetlana; Assouguem, Amine (Cabi Publishing, 2025)
Agritourism acts as a catalyst for rural revival by fostering economic diversity, cultural preservation, environmental sustainability, and community engagement. The integration of agriculture and tourism improves socio-economic welfare, preserves cultural heritage, and promotes sustainable resource utilization. Due to its contributions to rural economic and social advancement, the industry faces enduring obstacles, including insufficient infrastructure, constrained skill development, and limited market access. This paper analyzes the development, socio-economic effects, and growth prospects of agritourism in India in a worldwide framework. It underscores the significance of non-agricultural farm-based activities in bolstering rural economies, creating employment opportunities, and providing genuine rural experiences. The analysis underscores the importance of institutional support, legislative frameworks, and extension services in enabling farmers to become agri-entrepreneurs. Furthermore, it examines how value enhancement and digital technologies might enhance competitiveness, establishing agritourism as a viable and export-oriented industry. Agritourism serves as an additional revenue stream and a pivotal catalyst for rural change.
Keywords: agritourism; sustainable rural development; rural livelihood; agri-entrepreneurship; rural economy